Manuel Marzal S. J. Trajectory of one of the founders of the Instituto de Pastoral Andina - Sánchez Paredes, José (2009)
The religious and anthropological itinerary of Manuel Marzal S. J. is closely linked to the formation process of the Instituto de Pastoral Andina (IPA) that he helped to found. His Jesuit training process in American lands allowed him to discover, in an experiential and committed way, the existence of the indigenous populations of the Peruvian Andes. The discovery, first of the human face of the "Indian" and then of the "Indian face of God", prompts him to promote an institution that, from the Church, watches over the cultural and spiritual roots of the peasant religion. The context of the Second Vatican Council was the framework for this project in which Marzal promoted the study and rigorous investigation of indigenous cultural and spiritual traditions, convinced that, behind them, it is God himself who expresses himself. Thus, his participation in the elaboration of religious ethnographies, in the advice and training of pastoral agents, in the publication of numerous books on popular peasant Catholicism and, above all, his first impulse in the creation of the famous magazine Allpanchis Phuturinqa stands out. , which has served —and continues to serve— as a written repository of the rich tradition of study, promotion and evangelization of the Peruvian peasant population in the southern Andes.